Find the mistake:-

\({ a }^{ 2 }-{ a }^{ 2 }={ a }^{ 2 }-{ a }^{ 2 }\\ a(a-a)=(a+b)(a-b)\\ a=a+a\\ a=2a\)

Find the mistake:-

\({ a }^{ 2 }-{ a }^{ 2 }={ a }^{ 2 }-{ a }^{ 2 }\\ a(a-a)=(a+b)(a-b)\\ a=a+a\\ a=2a\)

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

## Comments

Sort by:

TopNewestyou can't divide by zero – U Z · 2 years, 7 months ago

Log in to reply

– Mrigank Krishan · 2 years, 7 months ago

which step??Log in to reply

– Ethan Godden · 2 years, 7 months ago

3rd step: (a-a) = 0 and dividing both sides by (a-a) is dividing by 0.Log in to reply

– Mrigank Krishan · 2 years, 7 months ago

OK now i got it, thanks a lot!!Log in to reply